2021
DOI: 10.1093/icesjms/fsab107
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for interpreting zooplankton metabarcoding and integrating molecular methods with morphological analyses

Abstract: Metabarcoding of zooplankton communities is becoming more common, but molecular results must be interpreted carefully and validated with morphology-based analyses, where possible. To evaluate our metabarcoding approach within the California Current Ecosystem, we tested whether physical subsampling and PCR replication affects observed community composition; whether community composition resolved by metabarcoding is comparable to morphological analyses by digital imaging; and whether pH neutralization of ethanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 51 publications
(65 reference statements)
4
22
0
Order By: Relevance
“…Bucklin et al (2019) reported significant positive correlations between V9 18S rRNA sequence numbers and microscopic counts for 7 taxonomic groups for which both types of data were available, with significant regressions for three groups: Calanoida, Gastropoda, and Chaetognatha. These results provided promising evidence that DNA metabarcoding using V9 18S rRNA can provide accurate classification and relative quantification for targeted zooplankton groups, which are important goals for applications for ecosystem monitoring (Lamb et al, 2018;Matthews et al, 2021).…”
Section: Integrative Morphological -Molecular Analysis Of Zooplankton...mentioning
confidence: 89%
See 3 more Smart Citations
“…Bucklin et al (2019) reported significant positive correlations between V9 18S rRNA sequence numbers and microscopic counts for 7 taxonomic groups for which both types of data were available, with significant regressions for three groups: Calanoida, Gastropoda, and Chaetognatha. These results provided promising evidence that DNA metabarcoding using V9 18S rRNA can provide accurate classification and relative quantification for targeted zooplankton groups, which are important goals for applications for ecosystem monitoring (Lamb et al, 2018;Matthews et al, 2021).…”
Section: Integrative Morphological -Molecular Analysis Of Zooplankton...mentioning
confidence: 89%
“…The accuracy and reliability of metabarcoding for (semi)quantitative analysis, including abundance or biomass, of zooplankton has been evaluated in previous studies (Elbrecht and Leese, 2015;Thomas et al, 2016;Bucklin et al, 2019). A consistent finding has been that quantitative estimates are more accurate for highly abundant taxonomic groups or species (e.g., Matthews et al, 2021).…”
Section: S3mentioning
confidence: 98%
See 2 more Smart Citations
“…There might also be biases in our relative prey contributions resulting from PCR, because we did not use PCR replicates. Although PCR biases can be problematic, especially in detecting rare OTUs 34,35 , more reliable results for major mesozooplankton prey could be obtained by using replicate samples. In addition, there is a potential risk of contamination in metabarcoding analysis, such as the inclusion of non-food DNA, laboratory contamination, symbionts of prey, and secondary predation 36 .…”
Section: Discussionmentioning
confidence: 99%